2008
DOI: 10.1007/s10444-008-9088-1
|View full text |Cite
|
Sign up to set email alerts
|

Alternative dual frames for digital-to-analog conversion in sigma–delta quantization

Abstract: Abstract. We design alternative dual frames for linearly reconstructing signals from Sigma-Delta (Σ∆) quantized finite frame coefficients. In the setting of sampling expansions for bandlimited functions, it is known that a stable rth order Sigma-Delta quantizer produces approximations where the approximation error is at most of order 1/λ r , and λ > 1 is the oversampling ratio. We show that the counterpart of this result is not true for several families of redundant finite frames for R d when the canonical dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…However, in [18] it is shown that even for higher order schemes one cannot "robustly" expect more than 1/N 2 error with the canonical dual for natural classes of frames, such as the harmonic frames. That is, in the case of harmonic frames, some oversampling rates achieve the correct approximation error but in large part it is not achieved.…”
Section: Msementioning
confidence: 99%
See 1 more Smart Citation
“…However, in [18] it is shown that even for higher order schemes one cannot "robustly" expect more than 1/N 2 error with the canonical dual for natural classes of frames, such as the harmonic frames. That is, in the case of harmonic frames, some oversampling rates achieve the correct approximation error but in large part it is not achieved.…”
Section: Msementioning
confidence: 99%
“…Higher order schemes in the finite frame setting have also been previously studied [3] and continue to be examined [5,7,18]. The higher order Σ∆ schemes for finite frames have provided a few surprises in that some of the early convergence rates for the group of frames being studies were somewhat unexpected given results from the band limited case.…”
Section: Introductionmentioning
confidence: 99%
“…A main focus of the subsequent work in [1,7,4,5,21] is to achieve better approximation rates (as the redundancy of the frame increases) for higher order Σ∆ schemes. In particular, one desires an approximation error of order O(N −r ) with an rth order Σ∆ scheme, where N is the number of frame vectors.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, one desires an approximation error of order O(N −r ) with an rth order Σ∆ scheme, where N is the number of frame vectors. It was proved in [21] that for Σ∆ schemes of order 3 or higher one cannot obtain these sought-for approximation rates, at least in the case of harmonic frames, if one uses canonical dual frames in the reconstruction. As a remedy, two main approaches have been developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation